Potential of 96% Etanol Extract of Bandotan Leaves (Ageratum conyzoides L.) as Larvasida Instar III Culex quinquefasciatus Say - Syiama Nofitri Yuningsih; Ichsan Luqmana Indra Putra (Jurnal Penelitian Pendidikan IPA, 2025)
The high number of filariasis cases in Indonesia requires efforts to control the population of Culex quinquefasciatus larvae. This study aims to analyse the concentration that is effective in killing Cx. quinquefasciatus larvae for 48 hours, and to analyse the LC50 and LT50 values of bandotan leaf extract within 48 hours. Bandotan leaves were collected from Jamblang village, Sleman, Yogyakarta. The leaves were extracted using 96% ethanol, diluted into five concentrations repeated 5 times. Third instar larvae of Cx. quinquefasciatus were obtained from the Salatiga Environmental Health Laboratory (BBLKL). Larval mortality was analysed using Kruskal-Wallis test and LC50 and LT50 probit analysis. The results obtained showed that 96% ethanol extract of bandotan leaves at concentrations of 1% (positive control) and 9% had an effect on larval mortality, with an LC50 value obtained of 3.88%. The LT50 values at concentrations of 0%, 1%, 3%, 5%, 7%, and 9% were 0 hours; 2.64 hours; 146.90 hours; 102.43 hours; 79, 24 hours; and 53.83 hours. The conclusion of this study is that 96% ethanol extract of bandotan leaves at the concentration used in this study does not have the potential to be used as a larvicide against Cx. quinquefasciatus.